Nanoparticle-assisted enhancement of therapeutic compounds in centella asiatica: a qualitative analysis - Sulong, Noor Anilizawatima; Mahmood, Mohamad Rusop; Mohsin, Hannis Fadzillah; Ahmad Noorden, Mohd Shihabuddin (Faculty of Pharmacy, 2025)
Centella asiatica (CA) is renowned for its medicinal properties, attributed primarily to its triterpenoid saponins: asiaticoside, asiatic acid, madecassoside, and madecassic acid. These compounds support collagen synthesis, wound healing, and exhibit antioxidant and anti-inflammatory properties. However, natural CA cultivation yields insufficient bioactive compounds to meet market demands. This study investigates zinc oxide nanoparticles (ZnONPs) as a means to enhance their production. ZnONPs were applied in varying concentrations (50, 100, 150, 200, and 250 mg/L) to hydroponically grown CA. Plants were harvested at intervals of 7, 14, 21, and 28 days, and analyzed using high-performance liquid chromatography (HPLC). ZnONPs significantly increased asiaticoside and madecassoside levels, particularly at 100 and 150 mg/L within 7 to 14 days. Asiaticoside peaked at 100 mg/L after 14 days, while madecassoside reached maximum levels at 150 mg/L ZnONPs concentration. Both compounds showed significant increases during the early stages of ZnONPs. Asiatic acid and madecassic acid also showed increased production, though the enhancement was less detected compared to asiaticoside and madecassoside. Asiatic acid exhibited significant peaks at 150 mg/L and 200 mg/L, while madecassic acid showed moderate enhancement, with peaks at 100 mg/L and 150 mg/L ZnONP concentrations. However, prolonged exposure and higher concentrations of ZnONPs led to a plateau or decline in compound production, likely due to nanoparticle toxicity. This study highlights the potential of nanotechnology in agriculture to sustainably enhance the production of valuable secondary metabolites in medicinal plants, meeting both pharmaceutical and cosmetic industry needs for consistent and high-quality bioactive compounds.